The Transformation and Economic Performance of North Lombok Regency After the 2018 Lombok Earthquake and Covid-19 Pandemic - Mohamad Zaki Taufik (Institut Pemerintahan Dalam Negeri, 2024)
In the short term, disaster events have a significant impact on economic growth and can drastically change the economy. After the Lombok earthquake disaster in 2018, the economy of North Lombok Regency experienced a negative contraction of 7.01% and then was tested again with the Covid-19 pandemic at the end of 2019 so that it again experienced a negative contraction of 13.32% in 2020. An analysis is needed to obtain an overview of the transformation and performance of the post-disaster economic sector in order to accelerate efforts to rehabilitate the regional economy as before and even more exciting than before. From the overlay analysis of the Static and Dynamic Location Quotient values, it is obtained that 6 (six) types of business fields are categorized as leading, 5 (five) types of business fields are categorized as prospective, 2 (two) types of business fields are categorized as mainstay and 4 (four) types of business fields are categorized as lagging. Based on the value of the Shift-Share component, overall economic growth in North Lombok Regency is classified as progressive. The economy of NTB Province contributes positively to the economy of North Lombok Regency. However, most of the business fields experienced slower growth and were not competitive with the same business fields in the NTB Province economy.